2019
DOI: 10.1097/dss.0000000000001811
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience With 100 Consecutive Patients Undergoing Neck Contouring With ATX-101 (Deoxycholic Acid): An Updated Report With A 2-Year Analysis

Abstract: BACKGROUNDDeoxycholic acid (DCA; ATX-101) injection was approved for the treatment of mild-to-moderate convexity associated with submental fat in 2015.OBJECTIVETo evaluate the experience with DCA injections in a clinical practice setting.MATERIALS AND METHODSThis ongoing, prospective, single-center, single-arm, observational study evaluated 100 consecutive patients treated with subcutaneous DCA (2 mg/cm2) injections (maximum 6 sessions at ≥1-month intervals). Treatment response was assessed using the clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Three separate large case series reporting real-world AEs were identified and reviewed. [8][9][10][11] One case series published an update resulting in 2 publications on the same cohort. 8,9 Nine additional case report publications of uncommon AEs were reviewed, with a focus on the timing of the AEs, number of subjects, treatment, and additional notes concerning recovery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three separate large case series reporting real-world AEs were identified and reviewed. [8][9][10][11] One case series published an update resulting in 2 publications on the same cohort. 8,9 Nine additional case report publications of uncommon AEs were reviewed, with a focus on the timing of the AEs, number of subjects, treatment, and additional notes concerning recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The 3 large case series of real-world experience in the literature are summarized in Table 2. [8][9][10][11] A total of 392 patients were reported, including 100 patients (aged 18-80 years) in the study reported by Shridharani, 8,9 202 patients The information in this table represents the different adverse reactions experienced by patients who received the Belkyra deoxycholic acid injection and those who received a placebo injection. This information is reported from the Belkyra product monograph published by Kythera Biopharmaceuticals, Inc. 7…”
Section: Large Real-world Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Male patients seek out ATX-101 treatment less often than females, but once they did, treatment-naive men returned for additional treatments at higher rates than women (19%–27% versus 12.9%–16.1%, respectively). 20 , 21 …”
Section: Selecting Patients For Atx-101 Treatmentmentioning
confidence: 99%
“…7 In our experience, temporary MMN injury occurs at a much lower rate in clinical practice than in the REFINE trials, with an incidence of 0.2% among ATX-101–treated patients in the CONTOUR trial. 16 Patient and physician concern about MMN injury may unnecessarily limit the treatment area [which is from the anterior border of the sternocleidomastoid muscle (SCM) to the anterior border of the contralateral SCM 21 ] and result in poor outcomes. Several cases attributed to MMN were likely pseudo-MMN, as has been described and proposed as direct injury or inflammation of the platysma, which could cause injury and dysfunction to the muscle.…”
Section: Managing Expectations Of Other Aes Associated With Atx-101mentioning
confidence: 99%